A case of venlafaxine-induced angioedema in an older adult. (September 2021) - Griffin, Hailee; Pearson, Scott; Linnebur, Sunny; Fixen, Danielle
Angioedema is a serious adverse event that can manifest as lower extremity edema, face swelling, rash, hives, and a swollen tongue, which can sometimes lead to airway constriction and death. It is a well-documented reaction within the angiotensin-converting enzyme inhibitor drug class, where the bradykinin pathway leads to angioedema. We report a case where a patient experienced angioedema after taking venlafaxine. We evaluated other antidepressants as potential treatment options for the patient. We further examined potential cross-reactivity between antidepressants in order to find alternative medications for patients that experience serious adverse effects.